Damage to fibre-polymer laminates caused by surface contact explosive charges. (15th September 2020) - Gargano, A.; Donough, M.; Das, R.; Mouritz, A.P.
Abstract: Blast response of composite materials is a crucial aspect for applications in engineering structures potentially subjected to extreme loadings. In this work, damage caused to fibre-polymer laminates by surface contact explosive charges is studied experimentally and numerically. In the blast tests, explosive charges placed in direct contact with glass or carbon fibre laminates cause partial or complete perforation due to the extremely high localised pressure generated by the blast. Damage is localised to the immediate vicinity of the explosive charge location, and includes fibre-matrix interfacial cracks, matrix cracks, delaminations, and broken and pulverised fibres. Finite element (FE) modelling can predict the types and amount of blast-induced damage. FE analysis reveals that the blast energy is absorbed by the laminates via fibre fracture and delamination cracking. Other types of damage, such as matrix cracking, absorb little energy. The FE models were validated against the results from experimental blast tests. Parametric analysis using the FE model is performed to determine the effects of several variables on the amount and types of damage, including the mass of the surface explosive charge and the thickness of the composite material.